2010
DOI: 10.21000/jasmr10010736
|View full text |Cite
|
Sign up to set email alerts
|

Leaching Potentials of Coal Spoil and Refuse: Acid-Base Interactions and Electrical Conductivity

Abstract: Unweathered overburden and coal processing wastes in southwestern Virginia contain varying amounts of carbonates and pyrite which affect water quality as spoil and refuse materials weather and leach. In addition to pH effects, these materials can input significant total dissolved solids (TDS) loads to drainage waters under both low and circumneutral pH conditions. The objective of this study was to evaluate acid-base interactions and overall TDS elution (as measured by electrical conductivity/EC) in leachates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 10 publications
1
34
0
Order By: Relevance
“…In a recent column study, Orndorff et al (2010) found that regardless of leachate pH, samples with significant levels of sulfides release much larger quantities of TDS over extended periods of time. Thus, even circumneutral mine discharges can contain high levels of sulfates as long as sufficient reactive carbonates are present in the source spoils.…”
Section: Background On Spoil Weathering and Tds Sourcesmentioning
confidence: 99%
See 4 more Smart Citations
“…In a recent column study, Orndorff et al (2010) found that regardless of leachate pH, samples with significant levels of sulfides release much larger quantities of TDS over extended periods of time. Thus, even circumneutral mine discharges can contain high levels of sulfates as long as sufficient reactive carbonates are present in the source spoils.…”
Section: Background On Spoil Weathering and Tds Sourcesmentioning
confidence: 99%
“…, and Na ? (Hartman et al 2005;Orndorff et al 2010;Agouridis et al 2012) with SO 4 2-and Ca 2? dominating the mass of ions released in circumneutral waters.…”
Section: Background On Spoil Weathering and Tds Sourcesmentioning
confidence: 99%
See 3 more Smart Citations